Fragments Along the Way: Minimalism as an Account of Some Stages in First Language Acquisition - Goodluck, Helen; Kazanina, Nina (Frontiers in Psychology, 2020)
We discuss two instances in which the minimalist model of syntax offers a potential account of children's linguistic behavior: the Merge analysis of phrase structure and the analysis of pronominal structures and other long distance dependencies. In each case, we need to understand the relationship between performance mechanisms (the mechanisms for language production and comprehension) and the syntax on which these mechanisms draw.